An Effective Routing Protocol with Guaranteed Route Preference for Mobile Ad Hoc Networks. (20th March 2014) - Chien, Feng-Tsun; Wu, Kuo-Guan; Chan, Yu-Wei; Chang, Min-Kuan; Su, Yi-Sheng
Battery power and queue conservation are critical issues in mobile ad hoc network (MANET). These two factors not only affect the delivery ratio but also the lifetime of the network. In this work, we will propose a simple and effective routing protocol to extend the lifetime and to evenly distribute the traffic loads of the networks as possible. Furthermore, a concept of serving capacity is introduced to reflect the level of congestion around a node. In this way, the proposed routing protocols can avoid network congestion and achieve higher packet delivery ratios. The extensive computer simulation is conducted to compare the proposed protocol against many existing routing protocols. The results show that the proposed routing protocol can have better performance in terms of queueing length, lifetime, and packet delivery ratio and have comparable end-to-end delays.